1999
DOI: 10.1046/j.1365-2133.1999.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of basic fibroblast growth factor and CD44 isoforms containing the variably spliced exon v3 (CD44v3) in normal skin and in epidermal skin cancers

Abstract: Previous in vitro studies have shown CD44 isoforms containing the alternatively spliced exon v3 (CD44v3) to be modified with heparan sulphate (HS) and to bind HS-binding basic fibroblast growth factor (bFGF). Here, we demonstrate that exogenously added bFGF is also bound in vivo by CD44v3-positive keratinocytes in normal skin and by tumour cells in basal cell carcinoma and squamous cell carcinoma (SCC), two skin cancers of keratinocyte origin. bFGF binding and CD44v3 expression were colocalized in cultured hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…FaDu cells were used as positive controls for the FGF-BP MAb 17 and A431 cells, for the bFGF MAb. 27 Both are SCC cell lines known to express the respective proteins. Tissue sections without primary antibody were used as negative controls.…”
Section: Fgf-bp Expression: Detection Of Protein By Western Blotting mentioning
confidence: 99%
“…FaDu cells were used as positive controls for the FGF-BP MAb 17 and A431 cells, for the bFGF MAb. 27 Both are SCC cell lines known to express the respective proteins. Tissue sections without primary antibody were used as negative controls.…”
Section: Fgf-bp Expression: Detection Of Protein By Western Blotting mentioning
confidence: 99%
“…CD44v3 and CD44v10) in addition to CD44s and CD44v3-10 (Epican) (6 -12). These CD44 isoforms have the same amino acid sequences at the two ends of the molecule but differ within the CD44 membrane-proximal region located at the external side of the membrane (5)(6)(7)(8)(9)(10)(11)(12). Different CD44 isoforms are also further modified by extensive N-and O-glycosylations and glycosaminoglycan additions (13)(14)(15).…”
mentioning
confidence: 99%
“…The predominant receptor for HA on the cell surface of keratinocytes is CD44 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). CD44 is encoded by a single gene that contains 19 exons (5).…”
mentioning
confidence: 99%
“…Because exon v3 of the CD44 proteoglycan is the only one containing this sequence in the context of the SG or SGSG motif, HS assembly is confined to this exon (30). The sequestering of HS-binding growth factors on the v3 exon of CD44 proteoglycan has been well documented (5)(6)(7)(8)(9)(10)(11)(12). Moreover, Sherman and colleagues (12) demonstrated that the addition of anti-CD44v3 mAb to limb bud mesenchymal cells cocultured in the presence of FGF-8, with UV-irradiated Namalwa cells expressing CD44v3-v10, markedly reduced the proliferation of the FGFR-bearing mesenchymal cells.…”
mentioning
confidence: 99%
“…CD44 proteoglycans can immobilize HS-binding growth factors, such as hepatocyte growth factor/scatter factor (5-7), VEGF (8), and heparin-binding epidermal growth factor (8)(9)(10), as well as FGF-2 (also known as basic FGF) (8,9,11), , and FGF-8 (12). Previous studies on the mode of action of FGF-2 and its association with HS identified a novel role for cell surface-and ECM-resident HS molecules in the formation of distinct FGF-2-HS complexes that are essential for binding FGF-2 to its cognate receptor (13) and subsequent signal transduction (14,15).…”
mentioning
confidence: 99%